O processo organizativo do MST através dos núcleos de base: a experiência do Assentamento João Batista II - Castanhal/PA - SANTANA, Midiã Olivia Bentes (Universidade Federal do Pará, 2014)
The present study aimed at examining the organizational process of the Landless Workers Movement / MST Nuclei in Nesting Base II John the Baptist, in the city of Fortaleza / Para. Aimed to identify the specific Social Profile of settlers organized in Nuclei in the settlement Base II John the Baptist; characterize the conditions of production and marketing via Core Base of the settlers of John the Baptist II and analyze political organization Nuclei Base nesting John Batista II. Based on historical and dialectical materialism, the walk methodological analysis was based on qualitative methodology and involved, as well as documentary and bibliographic research, field research, with the realization of semi-structured interviews with presentation and signed a consent form free and Clear - IC. The survey results indicate that the organizational cores via deconstituted Base was, however, the social collective through this organizational process are visible on settlements, leaving evidence of new experiences of collective work.